High-Tech Classroom Management: Effects of the Use of an App on Disruptive and On-Task Classroom Behaviours for Students with Emotional and Behavioural Disorder - Gabriel Cohen; Neil Martin (Behavioral Sciences, 2022)
Students with emotional behavioural disorders may exhibit extremely challenging behaviour that interferes with their academic achievement and social relationships. Failure at school frequently leads to a succession of poor life outcomes including increased rates of unemployment or underemployment. Increasing on-task behaviours and decreasing disruptive classroom behaviours is of crucial importance. If successful, this may promote positive experiences and outcomes in terms of effective learning, and, ultimately, greater opportunities in life. This study evaluated a high-tech approach to classroom management using an App* that offers elements of choice and predictability to students. Teachers were provided with two hours of training on how to upload lesson plans to their smartphone and how to broadcast onto screens in classrooms. A multiple-baseline design across four participants was used and the data suggested that the use of the App resulted in both increases in on-task behaviour and a reduction in disruptive classroom behaviour for all participants.